The Political Economy of Municipal Amalgamation: Evidence of Common Pool Effects and Local Public Debt. - Fritz, Benedikt; Feld, Lars P. (My University, 2015)
This paper investigates the political economy of after merger effects of the large scale municipal amalgamations in the German state of Baden-Württemberg in the early 1970s. By exploiting the huge variance in the amalgamation process in terms of number of participating municipalities, municipality size or amalgamation strategy we identify considerable common pool effects. Amalgamations can create a common pool, as the former independent municipalities have now access to more resources. Common pool exploitation is stronger the more municipalities participate and when municipalities amalgamate by annexation. Additionally, voter involvement is lower in amalgamated municipalities.
Keywords: Haushaltswesen; Gemeindegebietsreform; Finanzwesen; Öffentliche Einnahmen; Steuer; Gemeindegröße; Gemeinde; Zusammenlegung; Wirkung; Gemeindefinanzen; Finanzpolitik; Gemeindefusion; Eingemeindung; Wahlbeteiligung